PHYSICAL THERAPY AS A SUPPORT FOR PSYCHOTHERAPY IN TREATING BODY DYSMORPHIC DISORDER (BDD) - CASE STUDY - Mârza-Dănilă Doina; Mârza-Dănilă Roxana (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The treatment for Body Dysmorphic Disorder (or dysmorphophobia) includes antidepressant medication, cognitive-behavioral psychotherapy, psychoanalytical psychotherapy, hypnosis and others [2].Cognitive-behavioral psychotherapy was used for a patient with Body Dysmorphic Disorder, without any remarkable results, because even if the patient could bring himself to imagine the anxiogenic scenes, he could not manage to confront his fears. The psychotherapist called upon the services of physical therapy and over the course of three months, the patient's phobia regressed almost completely from his daily life. In conclusion, physical therapy can be considered, in Body Dysmorphic Disorder cases that are hard to manage through behavioral and cognitive therapies, as a support for psychotherapy.